The Price Elasticity of Natural Gas Demand in China: A Meta-Regression Analysis - Jian Chai; Huiting Shi; Xiaoyang Zhou; Shouyang Wang (Energies, 2018)
Since natural gas has become a new star in China’s energy mix, a reliable estimation of the price elasticity of natural gas demand is crucial if we are to understand how energy price changes affect natural gas consumption. In this paper, we conduct a Meta-regression analysis to quantitatively synthesize empirical estimates of the price elasticity of natural gas demand reported in previous studies, provide true underlying values, and explain the heterogeneity of the aforementioned estimates. The Fixed-effects model and ordinary least squares (OLS) are applied to estimate the regression models. As a result, this paper reports a mean elasticity of −1.521 and 0.410 for the short- and long-run own-price elasticity, separately; −0.762 and 0.008 for the short- and long-run cross-price elasticity-coal to natural gas, respectively; 2.122 and 1.884 for the short- and long-run cross-price elasticity-electricity to natural gas, separately; and 2.267 and 1.275 for the short- and long-run cross-price elasticity-oil to natural gas, respectively. Our results suggest that natural gas consumption increases with the decrease of its own and coal prices in the short term and rise of electricity and oil prices. It also shows that almost all heterogeneity can be explained by the type of data, sample period, models of analysis, geographical region, and type of consumer.